Granulocytic Myeloid-Derived Suppressor Cells (GR-MDSC) in Breast Milk (BM); GR-MDSC Accumulate in Human BM and Modulate T-Cell and Monocyte Function - Köstlin, Natascha; Schoetensack, Carolin; Schwarz, Julian; Spring, Bärbel; Marmé, Alexander; Goelz, Rangmar; Brodbeck, Gerhard; Poets, Christian F.; Gille, Christian (Frontiers in Immunology, 2018)
Nosocomial bacterial infections (NBI) and necrotizing enterocolitis (NEC) are among the main reasons for death in preterm infants. Both are often caused by bacteria coming from the infected infant’s gut and feeding with breast milk (BM) seems beneficial in their pathogenesis. However, mechanisms causing the protective effect of BM are only incompletely understood. Myeloid derived suppressor cells (MDSC) are myeloid cells with suppressive activity on other immune cells, recently described to play a role in mediating maternal-fetal tolerance during pregnancy and immune adaptation in newborns. Until now, nothing is known about occurrence and function of MDSC in BM. We analysed MDSC in BM and peripheral blood of breastfeeding mothers and found that granulocytic MDSC (GR-MDSC), but not monocytic MDSC (MO-MDSC), accumulate in BM, exhibit an activated phenotype and increased suppressive activity and modulate TLR-expression on monocytes. Furthermore, we found that the lactotrophic hormones prolactin and oxytocin do not induce MDSC from peripheral blood. This is the first study to describe MDSC with immune-modulatory properties in human BM. Our results point towards a role for MDSC in local immune modulation in the gut possibly protecting infants from NBI and NEC.